Impact of audio-visual storytelling in simulation learning experiences of undergraduate nursing students. (September 2017) - Johnston, Sandra; Parker, Christina N.; Fox, Amanda
Abstract: Background: Use of high fidelity simulation has become increasingly popular in nursing education to the extent that it is now an integral component of most nursing programs. Anecdotal evidence suggests that students have difficulty engaging with simulation manikins due to their unrealistic appearance. Introduction of the manikin as a 'real patient' with the use of an audio-visual narrative may engage students in the simulated learning experience and impact on their learning. A paucity of literature currently exists on the use of audio-visual narratives to enhance simulated learning experiences. Objective: This study aimed to determine if viewing an audio-visual narrative during a simulation pre-brief altered undergraduate nursing student perceptions of the learning experience. Design: A quasi-experimental post-test design was utilised. Participants: A convenience sample of final year baccalaureate nursing students at a large metropolitan university. Methods: Participants completed a modified version of the Student Satisfaction with Simulation Experiences survey. This 12-item questionnaire contained questions relating to the ability to transfer skills learned in simulation to the real clinical world, the realism of the simulation and the overall value of the learning experience. Descriptive statistics were used to summarise demographic information. Two tailed, independent group t -tests were used to determine statistical differences within the categories. Results: Findings indicated that students reported high levels of value, realism and transferability in relation to the viewing of an audio-visual narrative. Statistically significant results ( t  = 2.38, p  < 0.02) were evident in the subscale of transferability of learning from simulation to clinical practice. The subgroups of age and gender although not significant indicated some interesting results. Conclusions: High satisfaction with simulation was indicated by all students in relation to value and realism. There was a significant finding in relation to transferability on knowledge and this is vital to quality educational outcomes. Highlights: Audio visual (A-V) narratives added value to the simulation experience. Perceptions of transferability of learning increased with the use of AV narratives. Realism of the simulation contributed to satisfaction with the learning experience.